A Development of kiln shelf for firing ceramic from waste - T.saengchantara, Wanna; Rugthaicharoencheep, Sansanee; Boonwiset, Jutipa; Sriprasertsuk, Sutthima (Bulletin of Applied Sciences, 2022)
Bagasse ash is waste material from sugar production. Bagasse ash is high in SIO2, and some AL203; therefore it is used as starting material substitute for clay and alumina to produce ceramic kiln shelves. By synthesize cordierite from composition of bagasse ash, kaolin, alumina, and magnesite and fired at 1250 °C and 1300 °C. Then the composition exhibit the strongest cordierite and no other phase was selected to make the test samples. The 5, 10, and 15 portion of fine (-200+325 mesh) or course (-35+50 mesh) charcoal powder is added to the mixture to create pores in the final product. The mixture is then granulated size -35+50 mesh, and hydraulic pressed using 50 kg/cm2 and 180 kg/cm2 pressure. Green products are fired in electric kiln at temperature 1250°C. The results show that the formula with 46% ash, 11% kaolin, 14% alumina, 29% magnesite, and 10 portion of fine charcoal powder using 50 kg/cm2 pressure exhibit 1.94 g/cm3 bulk density, 29.9% apparent porosity 22.2MPa MOR and 4.09 x10*/°C COE. The pototype kiln shelve were prepared and tested the properties to compare with the commercial kiln shelves 3 brands. The properties of the commercial kiln shelves show 1.84-2.20 g/cm3 bulk density, 20.0-27.0 % apparent porosity, 10.7-15.0 MPa MOR and 2.50-3.63 x10-6/°C COE.